Urgency and Internal Control Practices in Islamic Boarding Schools in Indonesia: Principal and Accountant Perspectives - Febriani, Dewi; Riski Nurarifah, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
Internal control in Islamic boarding schools (pesantren) plays a crucial role in ensuring their sustainability. This research aims to analyze principals' perceptions regarding the importance of internal control for pesantren in Indonesia. The study employs a quantitative method with descriptive statistical analysis and differential testing using SPSS 26 software. The sole variable utilized is internal control, encompassing all its indicators as instruments. The findings of this research indicate that principals perceive internal control as highly significant for the management of their pesantren, serving as a foundation and guideline to ensure adherence to the institution's vision, mission, and initial objectives. Furthermore, the study identifies relatively sound practices of internal control within pesantren, although there is room for improvement according to accountants' perceptions. Additionally, the differential test results reveal that there is no significant difference between the groups of pesantren tested, both in terms of urgency as perceived by principals and in terms of practices as evaluated by accountants.